2015
DOI: 10.1021/acsbiomaterials.5b00319
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cellular Responses to Biodegradable Metal Zinc

Abstract: Biodegradable zinc (Zn) metals, a new generation of biomaterials, have attracted much attention due to their excellent biodegradability, bioabsorbability, and adaptability to tissue regeneration. Compared with magnesium (Mg) and iron (Fe), Zn exhibits better corrosion and mechanical behaviors in orthopedic and stent applications. After implantation, Zn containing material will slowly degrade, and Zn ions (Zn2+) will be released to the surrounding tissue. For stent applications, the local Zn2+concentration near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(117 citation statements)
references
References 67 publications
4
111
1
1
Order By: Relevance
“…When compared with Mg materials, the pH change and hydrogen gas release for Zn materials are much less because of their different corrosion mechanism 5c,6a,12,13. It has been previously indicated that Zn ion affects the cell responses in a concentration‐dependent manner in vitro 7b,8,14. Although Zn ion plays significant and beneficial roles in cell behaviors and functions,7b,8 overdosed Zn ion could induce harmful cellular responses in vascular smooth muscle cells and endothelial cells after its concentration reached a limit of 3.9 and 5.2 µg mL −1 , respectively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with Mg materials, the pH change and hydrogen gas release for Zn materials are much less because of their different corrosion mechanism 5c,6a,12,13. It has been previously indicated that Zn ion affects the cell responses in a concentration‐dependent manner in vitro 7b,8,14. Although Zn ion plays significant and beneficial roles in cell behaviors and functions,7b,8 overdosed Zn ion could induce harmful cellular responses in vascular smooth muscle cells and endothelial cells after its concentration reached a limit of 3.9 and 5.2 µg mL −1 , respectively .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously indicated that Zn ion affects the cell responses in a concentration‐dependent manner in vitro 7b,8,14. Although Zn ion plays significant and beneficial roles in cell behaviors and functions,7b,8 overdosed Zn ion could induce harmful cellular responses in vascular smooth muscle cells and endothelial cells after its concentration reached a limit of 3.9 and 5.2 µg mL −1 , respectively . In the present study, the Zn ion concentration reached 40 and 60 µg mL −1 after 3 days culture with endothelial cells and preosteoblasts, respectively (Figure d,e and Figure c,d), which are significantly higher than the concentration limits for normal cell behaviors and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cellular responses to high extracellular Zn 2+ will impact the healing process and biocompatibility with zinc-bearing implants [16]. Furthermore, the response of the host's immune system will determine whether the implant becomes biointegrated and continues to function as designed, or encapsulated in a dense fibrous tissue that may compromise the intended function of the implant.…”
Section: Pure Zincmentioning
confidence: 99%
“…The cellular response of human bone marrow mesenchymal stem cells (hMSC) and human vascular cells (HCECs, HASMC, HAEC) to Zn 2+ was recently investigated [16,26,69,70]. According to Zhu et al [70], Zn biomaterial can support hMSC adhesion and proliferation and zinc ions can lead to enhanced regulation of genes, cell survival/growth and differentiation, extracellular matrix (ECM) mineralization, and osteogenesis.…”
Section: In Vitro Examinationmentioning
confidence: 99%
See 1 more Smart Citation